let X be set ; :: thesis: for S being SigmaField of X
for M being sigma_Measure of S
for G, F being sequence of S st M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds
( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) holds
M . (meet (rng F)) = (M . (F . 0)) - (M . (union (rng G)))

let S be SigmaField of X; :: thesis: for M being sigma_Measure of S
for G, F being sequence of S st M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds
( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) holds
M . (meet (rng F)) = (M . (F . 0)) - (M . (union (rng G)))

let M be sigma_Measure of S; :: thesis: for G, F being sequence of S st M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds
( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) holds
M . (meet (rng F)) = (M . (F . 0)) - (M . (union (rng G)))

let G, F be sequence of S; :: thesis: ( M . (F . 0) < +infty & G . 0 = {} & ( for n being Nat holds
( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) implies M . (meet (rng F)) = (M . (F . 0)) - (M . (union (rng G))) )

assume that
A1: M . (F . 0) < +infty and
A2: ( G . 0 = {} & ( for n being Nat holds
( G . (n + 1) = (F . 0) \ (F . n) & F . (n + 1) c= F . n ) ) ) ; :: thesis: M . (meet (rng F)) = (M . (F . 0)) - (M . (union (rng G)))
A3: union (rng G) = (F . 0) \ (meet (rng F)) by ;
A4: M . ((F . 0) \ (union (rng G))) = M . (meet (rng F)) by ;
M . ((F . 0) \ (meet (rng F))) <> +infty by ;
then M . (union (rng G)) < +infty by ;
hence M . (meet (rng F)) = (M . (F . 0)) - (M . (union (rng G))) by ; :: thesis: verum